PENGARUH PENGEMBANGAN EKOWISATA BERBASIS MASYARAKAT TERHADAP PERUBAHAN KONDISI EKOLOGI, SOSIAL BUDAYA DAN EKONOMI DI DESA WISATA WATURAKA, DAERAH PENYANGGA TAMAN NASIONAL KELIMUTU, KABUPATEN ENDE, NUSA TENGGARA TIMUR (NTT) - Andreas Gilbertus Waja; Paulus K. Un; Norman P.L.B. Riwu Kaho (Wana Lestari, 2019)
Waturaka village is one of the village located in Kelimutu District, Ende regency, East Nusa Tenggara provinces. Waturaka villages is an example of the application of the community-based ecotourism in Ende district. Ecotourism or ecotourism is one of the activities of tourism that is environmentally oriented by prioritizing aspects of nature conservation, aspects of socio-economic empowerment of local communities and aspects of learning and education. The development of ecotourism affects people in ecological, economic and socio-cultural aspects. The aim of this research to analyze ecological, economic and socio-cultural conditions in Waturaka Village after community-based ecotourism applications in this researt is changes. The total of respondents in the data collection was 52 peoples purposevely selection. The research method used descriptive method by analyzing respondents' answers, the results are tabulated in the form of frequency tables to present ecological, economic and socio-cultural influences with the existence of community-based ecotourism management. The analysis tools used are validity and reliability tests to test questionnaires and statistical T tests to test hypotheses, the calculation in processing this data is assisted by Microsoft Exel program and SPSS 16 saftware. T-test results of economic criteria show that the value of tcount (45.3673) > ttable (2.007) so that HI is accepted and H0 is rejected, ecological criteria tcount (4.3111) > ttable (2.007) so that Hl is accepted and H0 is rejected, socio-cultural criteria tcount (18.8832) > ttable (2.007) so Hl is accepted and HO is rejected. From the results of the t test as a whole shows that there are very significant differences in ecological, economic and socio-cultural conditions before and after the development of community-based ecotourism in Waturaka Village. The development of community-based ecotourism is precisely implemented in Waturaka Village, as evidenced by the results of hypothesis testing showing that after the existence of ecotourism there are changes in ecological, economic and socio-cultural conditions that are better than before the existence of ecotourism.